Lesion morphology at 7 Tesla MRI differentiates Susac syndrome from multiple sclerosis - Würfel, Jens Thomas; Jarius, Sven (Multiple sclerosis journal, 2012)
Background:Although an orphan disease with still obscure aetiopathogenesis, Susac syndrome has to be considered as differential diagnosis in multiple sclerosis (MS), since its clinical presentation and paraclinical features including routine magnetic resonance imaging (MRI) findings partially overlap.Objective:We aimed to study a potential benefit of 7T MRI for (i) the differentiation between Susac syndrome and MS and (ii) the clarification of pathogenesis of Susac syndrome.Methods:Five patients suffering from Susac syndrome, 10 sex- and age-matched patients with relapsing?remitting MS (median Expanded Disability Status Scale (EDSS) score 1.5) and 15 matching healthy controls were investigated at 7 Tesla MRI. The protocol included T1-weighted MPRAGE, T2*-weighted FLASH, and TIRM sequences.Results:Almost all T2* FLASH lesions in patients with MS were centred by a small central vein (325 lesions; 92%) and often showed a small hypointense rim (145 lesions; 41%). In contrast, white matter lesions in Susac syndrome exhibited a perivascular setting significantly less frequently (148 lesions; 54%, p=0.002), and very rarely exhibited a hypointense rim (12 lesions; 4%, p=0.004). Furthermore, in addition to callosal atrophy, Susac patients showed cerebrospinal fluid-isointense lesions within the central part of corpus callosum that are not commonly seen in MS.Conclusion:At 7T MRI, plaques in MS patients and patients with Susac syndrome differed substantially with respect to morphology and pattern. Thus, lesion morphology at 7T (i) may serve as a marker to distinguish Susac syndrome from MS and (ii) reflects a different pathophysiological mechanism underlying Susac syndrome, for example microinfarction rather than demyelination.